INCREASING THE COMPETITIVENESS OF COMMERCIAL BANKS THROUGH TRADITIONAL OPERATIONS IN THE BANKING SYSTEM - Khaberdiev Bekzod Oktamovich (Journal Park Publishing, 2022)
In this state description of traditional banking, their role in the economy, banking system reforms, expansion of convenient remote banking services offered to the public and business, such as Internet banking, SMS banking and mobile banking, based on modern information and communication technologies. Attention is also paid to the system of remote management of bank accounts of enterprises and organizations, and also allows to significantly increase the popularity of such services.
Keywords: сredit, crediting, deposit, cash, capital, pawnshop, currency market, internet banking